Position of Imam Malik bin Anas on deviant sects - Esmail, Allaa Eddin Muhammad; Hashim, Jamil; Ahmad, Masitoh (Kolej Universiti Islam Sultan Azlan Shah, 2014)
The study attempts to highlight the position of Imam Malik bin Anas on deviant sects which emerged and developed during his time. It discusses the views of Imam Malik on other Muslim sects like Shi'its and its school of thoughts, Qadarites, where he authored a specific book and a chapter in his "Muwatta" in response to their central teachings, Khariji, Murji"it and Mu'tazilites. This paper also discusses the views of Imam Malik and his response to important issues related to those sects such as "al-mutasyabihat" and the creation of Al-Quran. Imam Malik's ways and methods in dealing with those sects are also highlighted.